"How'd you sleep?" measuring business travelers' sleep quality and satisfaction in hotels. Issue 3 (13th August 2018) - Chen, Hsiangting Shatina; Severt, Kimberly; Shin, Yeon Ho; Knowlden, Adam; Hilliard, Tyra W.
Abstract : Purpose: The purpose of this paper is to explore business travelers' sleep experience in hotels by measuring sleep quality and determining the extent to which hotel attributes, demographic characteristics, and hotel quality level influence their sleep quality while staying in hotels. Design/methodology/approach: This study utilized a self-reported survey to obtain data from business travelers who have stayed in a hotel at least two nights for a business trip in the past 30 days. A total of 304 business travelers were surveyed in this study. Findings: The results indicated that there was a difference in the factors that influenced business travelers' overall satisfaction with sleep in mid-scale (2.5-3.5 stars) vs upscale hotels (4+stars). The findings showed that business travelers generally had lower sleep quality at hotels and they were more likely affected by noise both outside and inside the guestroom, as well as material elements inside the room. Originality/value: This study represents a pioneering attempt at exploring business travelers' sleep quality and satisfaction with sleep in hotels. Furthermore, this study contributes to the limited research addressing sleep quality as a fundamental function of hotel services. Also, this is the first study to measure business travelers' sleep quality in hotels by using the sleep quality scale.